Gastrointestinal Parasites in Birds at Taman Rusa, Aceh Besar - Sari, Rahmah; Dwitama, Fajri; Fahrimal, Yudha; Daud, Razali; Riandi, Lian V.; Hasan, M.; Helmi, Teuku Z. (Aceh Journal of Animal Science, 2025)
Captive animals are not immune to infectious diseases, including parasitic infections that can be fatal. Prolonged periods of captivity can increase the likelihood of transmission between animals and humans. This study was conducted to identify and document the parasites that infect birds housed at Taman Rusa in the Aceh Besar District. The collected fecal samples were placed in labeled sample bottles containing formalin and stored in ice boxes. Fecal samples were collected, preserved in 10% formalin, and examined using flotation, sedimentation, formol-ether, and modified Ziehl-Neelsen techniques. The data obtained from the examination of the fecal samples were tabulated and descriptively analyzed. The results of fecal sample examinations carried out on 60 birds (representing 28 species) indicated that 39 birds (19 species) were infected with parasites. The nematode class included Heterakis sp. (3.33%), Capillaria sp. (13.3%), Trichuris sp. (6.67%), and Strongyloides sp. (8.3%). The cestode class included Hymenolepis sp. (10%), while the trematode class included Neodiplostomum sp. (1.67%). Additionally, the class Conoidasida protozoa included Eimeria sp. (33.3%) and Isospora sp. (1.67%). The highest prevalence of helminth infection was observed in Capillaria sp. infection (13.3%), while Eimeria sp. exhibited the highest prevalence of protozoan infection (35%). The findings deliver valuable guidance for veterinary health management, disease surveillance, and biosecurity strategies in avian conservation facilities. The identification of parasites with established pathogenic and zoonotic potential, including Strongyloides sp. and Capillaria sp., highlights the significance of these results for both avian health and potential public health risks.